Impact of cognitive ability in young adult age on risk of cardiovascular disease and presence of subclinical carotid plaques among men aged 60 years. (3rd October 2022) - Norberg, M; Liv, P; Naslund, U; Wester, P; Nordin, S
Abstract: Background: A clear association between low cognitive ability in early adult life and increased risk of premature cardiovascular diseases (CVD) has been demonstrated [1]. However, the mechanisms for this relationship are not fully understood. Also, despite the evidence on low early cognitive ability being a risk factor for CVD, specific CVD prevention studies in this group has not been reported and low cognitive ability has not been mentioned in clinical guidelines for prevention of CVD. Purpose: To clarify the interrelationships between early adult life cognitive ability and late middle-life health behaviors and the risk of CVD and presence of subclinical carotid plaque. Methods: Register-data from psychological testing of men at age 18–19 years in the Swedish Enlistment Battery was used (n=1009), and early cognitive ability was calculated as the mean of four subtests on a scale from 1 to 9 (logical-inductive ability, verbal ability, visuospatial ability and technical understanding). A lifestyle index on a scale from 4 to 12, which was calculated as the sum of self-reported diet, physical activity, smoking and alcohol consumption, where each behavior was divided into 3 levels and the most health-promoting level was the highest level, as well as clinical CVD risk factors were collected at age 60 years within the VIPVIZA RCT (Västerbotten Intervention Program – Visualization of subclinical Atherosclerotic disease for optimum cardiovascular prevention) [2]. Risk of CVD was calculated as SCORE and presence of carotid plaques was identified, based on ultrasonography and defined according to Mannheim consensus [2]. Early cognitive ability's association to SCORE and presence of carotid plaques was assessed using linear and logistic regression, respectively. The linear regression was performed using restricted cubic splines to account for non-linearity. Results: Early cognitive ability and the lifestyle index were normally distributed (mean 4.24, SD 1.12 and mean 9.95, SD 1.484, respectively). Mean of SCORE was 2.6%, SD 1.4. Carotid plaques were observed among 61%. A statistically significant negative association between early cognitive ability and SCORE was found (p=0.009, Figure 1). Higher early cognitive ability was also associated with a decreased risk for carotid plaques, with an odds ratio 0.86 for each increase of one point in cognitive ability (95% CI: 0.76–0.96, p=0.007). Conclusion: Among men, higher cognitive ability at age 18–19 years is associated with lower risk of CVD and lower risk of having carotid plaque at age 60 years Additional modelling analyses are warranted to clarify the mediating and moderating roles of socioeconomic position, lifestyle and clinical CVD risk factors on the path between early cognitive ability and risk of CVD and subclinical atherosclerosis. This may guide development of tailored interventions to reduce the inequity in CVD due to cognitive ability. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Swedish Research CouncilRegion Västerbotten